2020
DOI: 10.3390/ani10091457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Laetiporus sulphureus-Fermented Wheat Bran on Growth Performance, Intestinal Microbiota and Digesta Characteristics in Broiler Chickens

Abstract: This study investigated the effects of a Laetiporus sulphureus-fermented wheat bran (LS) supplementation on the microbiota and digesta characteristics of broiler chickens. Two hundred and forty male broilers (Ross 308) were randomly allocated into three groups fed with a corn–soybean-based diet (control), and the control diet being replaced with 5% wheat bran (WB) and 5% LS, respectively. Each group had four replicates and 20 birds per pen. Metagenomics analysis results of the ileum microbiota showed that, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…During the fermentation process, various essential nutrients are produced, such as vitamins, organic acids, amino acids, and small-size peptides, which may further increase the nutritional value of by-products ( Feng et al, 2007 ; Chen, 2010 ), thereby extending the use of by-products such as WB in the poultry industry. Previous studies of fermented WB mainly focused on indicators such as growth performance, intestinal health, immune performance, and economic benefits, whereas systematic evaluation of the nutritional value of fermented bran in poultry has not been widely conducted ( Wanzenböck et al, 2020 ; Lin and Lee, 2020 ). Accurately quantifying the efficiency of metabolizable energy utilization of fermented soybean meal has led to the wide use of this material in the industry ( Soumeh et al, 2019 ; Ping et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the fermentation process, various essential nutrients are produced, such as vitamins, organic acids, amino acids, and small-size peptides, which may further increase the nutritional value of by-products ( Feng et al, 2007 ; Chen, 2010 ), thereby extending the use of by-products such as WB in the poultry industry. Previous studies of fermented WB mainly focused on indicators such as growth performance, intestinal health, immune performance, and economic benefits, whereas systematic evaluation of the nutritional value of fermented bran in poultry has not been widely conducted ( Wanzenböck et al, 2020 ; Lin and Lee, 2020 ). Accurately quantifying the efficiency of metabolizable energy utilization of fermented soybean meal has led to the wide use of this material in the industry ( Soumeh et al, 2019 ; Ping et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [17] found that fermentation of wheat bran by Saccharomyces and Lactobacillus increased the content of water extractable arabinoxylan by 3-4 times, increased the content and bioavailability of soluble dietary fiber and total free phenolic, and degraded over 20% of phytic acid. Additionally, adding 5% dry fermented wheat bran (FWB) to broilers (Ross 308) diets improved the growth performance, increased the Lactobacillus counts in ileum, and maintained the beneficial intestine environment [18]. Zhang et al [19], Lee et al [20] and Teng et al [21] found that the solid-state fermented wheat bran had promoting effects on growth performance, nutrient digestibility and anti-inflammation in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…When stimulated by pathogenic bacteria, the animal initiates an immune response, which leads to a cytokine storm. However, excessive inflammation can reduce animal performance and even lead to death [ 14 , 15 ]. On the other hand, when the oxidative pressure is high, animals are not able to eliminate the damage caused by free radicals to cells and/or organs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%